Timah Tasoh Resort / Mazziatul Feesya Salleh ... [et al.] - Salleh, Mazziatul Feesya; Mat Saad, Noor Afzan; Nazril, Nazariah; Saleh, Muzaimah; Mat, Afiza (2001)
Timah Tasoh Resort is a partnership company stated at Empangan Timah Tasoh, Perlis. They run a resort and focus on tourism sector. They started their first operation on 1 December 2002.